Neurosciences and mental health: New frontiers of clinical research - Andrade, Andreus Cristhian Linhares; Minosso, Fernanda Barboza; da Silva, Carolina Ribatski; Hollen, Fabiany Lago Barbosa; Karhawi, Naíma Santos; Pinarello, Aryanne Zorzi; Butakka, Jessica Nayara de Barros; Franzner, Karina Augusta Sarto Nery; Jardim, Isabelle Amable Pereira; Nogueira, Maria Eduarda Pinheiro; Lima, Clara Luz de Souza; Passos, João Pedro Castoldo (Seven Editora, 2024)
This chapter explores the new frontiers of clinical research in neuroscience applied to mental health, highlighting recent advances and their implications for psychiatric practice. The integration between neuroscience and mental health has allowed a deeper understanding of mental disorders, with the identification of biomarkers that help in the diagnosis and personalization of treatment. Therapeutic interventions based on neuroplasticity, such as Transcranial Magnetic Stimulation (TMS) and neurofeedback, have been shown to be effective in modulating brain activity and improving symptoms in patients resistant to conventional treatment. Emerging technologies such as artificial intelligence, virtual reality, and brain-computer interfaces are reshaping the future of psychiatry, enabling a more precise and personalized approach. However, these advances bring ethical and practical challenges, including privacy issues, equity in access, and the need for regulation. The chapter concludes that the integration of these innovations into clinical practice must be accompanied by a commitment to ethics, accessibility, and humanization of care. DOI:https://doi.org/10.56238/sevened2024.026-034